Psikoedukasi Trauma dan Pelatihan Tas Siaga Bencana Pada Anak dan Remaja di Desa Pukdale - Fomeni Mela, Angelina; Chantika Willa, Indri Ariani; Waworuntu, Rut Venny; Mustakim, Victoria; Ngeni Wewo, Stevania; Eunike, Lucya; Zeah Alzuhri, Zania; Christine Pello, Shela (Yayasan Inspirasi El Burhani, 2024)
Introduction: The tropical cyclone Seroja disaster that hit East Nusa Tenggara in April 2021 caused significant material and non-material losses so that many residents, including children and adolescents, experienced trauma due to this disaster. This study aims to provide an understanding of post-disaster trauma in children and adolescents and improve their preparedness through psychoeducation and training in making disaster preparedness bags. Method: used involved pre-test and post-test evaluations to assess the effectiveness of this program. Results: the study showed that psychoeducation and training activities succeeded in improving the understanding and preparedness of children and adolescents in dealing with trauma and disasters, with an N-Gain Score of 60, included in the moderate category. Conclusion: This program has a positive impact in helping them manage their emotions and increasing their preparedness in dealing with emergency situations.